Analysis Impact of Covid-19 Outbreak on Performance of Commercial Conventional Banks: Evidence from Indonesia - Siska, Elmira; Gamal, Awadh Ahmed Mohammed; Ameen, Ali; Amalia, Mekar Meilisa (IJOSMAS, 2021)
The banking industry serves a crucial role in the economy. Unpredictable conditions, such as the Covid-19 outbreak, have had a widespread effect on global health as well as banking. This study is to analyze the impact of the Covid-19 outbreak on solvency (CAR), profitability (ROA and NIM), and efficiency (OEOI), liquidity (LDR), and risk profile (NPL) of Commercial Conventional Banks in Indonesian. This study is a quantitative research with a descriptive approach. Secondary data from Indonesian Banking Statistics were used in this study. Data was collected 8 months before the pandemic Covid-19 (July 2019 - February 2020) and 8 months (April 2020 - November 2020) after the first case of Covid-19 was recorded in Indonesia on March 2, 2020. The finding of this study revealed that there was a significant difference in term of profitability, efficiency, liquidity, and credit risk of Commercial Conventional Banks before and after Covid 19. Meanwhile the level of solvency was not significantly different. However, the overall performance of Commercial Conventional Banks remains at a healthy level. As the pandemic is ongoing and continues to affect on the economy, our suggestion that banking resilience should be strictly monitored in the coming years.